1998
DOI: 10.1002/1529-0131(199804)41:4<596::aid-art6>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect betweenIL-10 andbcl-2 genotypes in determining susceptibility to systemic lupus erythematosus

Abstract: The results suggest that individuals carrying specific genotypes of both bcl-2 and IL-10 are at significant risk of developing SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
5

Year Published

1999
1999
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 26 publications
3
88
5
Order By: Relevance
“…13 Different polymorphisms were identified both in the 5' flanking region [14][15][16][17][18][19][20] and, more recently, in the transcribed region 21 of the IL10 gene including two microsatellites at position À4000 (IL10 15 ) and À1100 (IL10 16 ). One of the two microsatellites, IL10.G, has been shown to be associated to SLE by three independent studies, including ours [22][23][24] although this was not supported by a fourth work. 25 In our study the IL10.G-140bp allele was significantly increased in Italian SLE patients.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…13 Different polymorphisms were identified both in the 5' flanking region [14][15][16][17][18][19][20] and, more recently, in the transcribed region 21 of the IL10 gene including two microsatellites at position À4000 (IL10 15 ) and À1100 (IL10 16 ). One of the two microsatellites, IL10.G, has been shown to be associated to SLE by three independent studies, including ours [22][23][24] although this was not supported by a fourth work. 25 In our study the IL10.G-140bp allele was significantly increased in Italian SLE patients.…”
Section: Introductionmentioning
confidence: 57%
“…[22][23][24] The association with the IL10 microsatellite could be due to linkage disequilibrium with some causal variation in another closely linked gene. Three genes belonging to the IL10 family (IL19, IL20 and IL24) have been recently mapped immediately telomeric to IL10 at a distance of 60 , 82 and 112 kb respectively from IL10G, and are possible candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Alleles of all three genes were found to be associated with SLE in a study of Mexican-Americans [61]. In the same study, a synergistic effect between alleles of the IL-10 and bcl-2 genes in determining susceptibility SLE was found [61].…”
Section: Studies Of Candidate Genesmentioning
confidence: 91%
“…Some evidence has been obtained for possible association with SLE and alleles at Bcl-2, CTLA4, the T cell receptors, prolactin, tumor necrosis factor (TNF) and TNF receptors. [92][93][94][95][96][97][98] Even in aggregate, however, these effects are too small to explain the genetics of SLE. Therefore, other genes still remain to be identified.…”
Section: Fc␥ Receptorsmentioning
confidence: 99%
“…106 To date, no study has observed an association between the IL10.R microsatellite and SLE. Mehrian et al 92 …”
Section: Interleukin-10mentioning
confidence: 99%